The Effect of Circuit Trainingon The Students’ Physical Fitness at PGRI University Pontianak - Zusyah Porja Daryanto; Ashadi Cahyadi; Ferry Suyitnio (Jurnal Pendidikan Olah Raga, 2025)
AbstractThis study was to examine the effect of circuit training on the physical fitness of students at Universitas PGRI Pontianak. The research employed a pre-experimental method. The subjects are 20 students from the Physical Education study program year 2023. Data were collected using the Bleep Test. The data analysis techniques included descriptive analysis, normality testing, t-test, and effect size analysis. The mean score of pre-test was 47.55, and the post-test score was 51.40. The data were normally distributed, with normality values of 0.963 for the pre-test and 0.440 for the post-test. The results of the t-test were 6.956, which is greater than the t-table value 1.729, with an effect size of 6.67. Therefore, it can be concluded that circuit training has a significant effect on students’ physical fitness, and the implementation of circuit training can serve as a basis for lecturers and coaches in designing more systematic and measurable training programs in higher education settings.